A Cambodian Dancer in a Displaced Persons’ Camp - Toni Shapiro-Phim (Music & Minorities, 2021)
The more than a quarter of a million Cambodians in camps on the Thai side of the Cambodia-Thailand border in the late 20th century are referred to, in Khmer, as chun pies khluon. This translates into English as “refugees,” but means, literally, “those who are escaping” or “people on the run.” Existing between a then-recent past of devastating loss and a future as yet unknown, they remained in an unsettled situation of physical precarity for more than a decade as many of the camps along that border were in an active war zone.